「地域の物語」の再生と自治の諸相 - Yamada Keijirou 山田圭二郎; Fujikura Hideyo 藤倉英世; Hagai Masami 羽貝正美; Nishi Ken 西研; Evellin-Katsuki Keiko エヴラン・勝木慶子 (Projets de Paysage)
Local authorities and territories are "places" in which various "actors" compete while pursuing a common interest and improving the social system. By adopting this perspective and analysing Japanese and French cases dating back to the 1960s, this article seeks to explain how small local authorities or regions faced with a threat to their survival managed to overcome crises and understand the part played by the landscape in this process. To do so we applied our own approach which we have termed as “a diagram of the social-spatial structure” method. The result of our study confirmed the existence of a process of "regeneration of local history" consisting of four stages and enabled us to identify the following key concepts: "self-understanding", the "internalisation of otherness" and the "space of the public sphere". In this process, the landscape fosters a "rewriting of history", changing the understanding of "the meaning of a past heritage while creating future values".